KINERJA INTENSITAS PENCAHAYAAN BANGUNAN: STUDI KASUS MALANG CREATIVE CENTER - Romadhoni, Nur; Subiyantoro, Heru (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Abstract: Building Lighting Intensity Performance: Case Study of Malang Creative Center. This research aims to determine the light intensity in the Malang Creative Center building and provide suggestions for solutions to rooms that function as places for creative economy activities with less light intensity. Creative activities require lighting to support user productivity in carrying out activities in buildings (Le et al., 2022; Matthew & Nico, 2023). Lighting in a building is influenced by several factors, including the size of the openings, the orientation of the openings, the use of materials and color in the space. The aim of this research is to find out and identify the intensity of light in several spaces which are a place for creative actors to carry out activities at the Malang Creative Center. By using a comparative method, light intensity data in several research object rooms will be compared with standard data or ideal light intensity for rooms that function as work spaces. Field measurement data was obtained from a direct measurement process carried out longitudinally from 09.00-15.00 WIB, while standard data or ideal light intensity for work spaces was obtained from literature studies. From the research process carried out, it was found that there was one room whose light intensity did not meet the standards starting at 09.00-15.00 WIB, while the other 3 rooms showed ideal values in the time range 09.00-13.00, but at 13.00-15.00 these rooms also show numbers that are not ideal.